Hệ thống AI tác nhân trong phân tích nội dung tự động của tập dữ liệu giáo dục - Trần, Trung; Đỗ, Mạnh Hùng; Nguyễn, Thị Kim Sơn (Tạp chí Giáo dục, 2025)
In the context of accelerating digital transformation and advancement of artificial intelligence, this paper presents the implementation of an agent-based artificial intelligence (AI Agent) system for the automatic analysis of domain specific educational content. The study successfully deployed the “Agent AI Edu” system, powered by the Qwen2.5-7B-Instruct model, on a low-spec server, demonstrating high performance and cost-efficiency. Agent AI Edu offers key features including lecture materials content ingestion and processing, automatic summarization, slide generation, test creation, and domain-specific virtual assistant capabilities. The experimental results indicate that the system significantly reduces educators’ workload while enhancing the quality of educational content and teaching methodologies. The study proposes integrating AI Agents into Learning Management Systems (LMS) to build an intelligent digital education ecosystem that supports personalization and real time feedback in teaching and learning.